2006
DOI: 10.1161/01.atv.0000222017.05085.8e
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin Induces Transdifferentiation of Monocytes Into Functional Endothelial Cells

Abstract: Objective-Pleiotrophin (PTN) is a cytokine that is expressed by monocytes/macrophages in ischemic tissues and that promotes neovascularization, presumably by stimulating proliferation of local endothelial cells. However, the effect of PTN on monocytes/macrophages remains unknown. We investigated the role of PTN in regulating the phenotype of monocytes/macrophages. Methods and Results-RT-PCR, real-time PCR, and fluorescence-activated cell sorter analysis revealed that the expression of PTN by monocytic cells le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 25 publications
2
57
0
3
Order By: Relevance
“…27,47,48 Several groups have identified bone marrow-derived endothelial precursor cells and demonstrated that myeloid progenitor, dendritic, and mononuclear cells can differentiate into cells of the endothelial lineage. 3,[6][7][8][9]46,[49][50][51] These new endothelial cells circulate and ultimately contribute to blood vessel formation during tumor development and metastasis. 49,52 However, the origin of cells that ultimately line tumor blood vessels and specific proteins required for tumor vasculogenesis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,47,48 Several groups have identified bone marrow-derived endothelial precursor cells and demonstrated that myeloid progenitor, dendritic, and mononuclear cells can differentiate into cells of the endothelial lineage. 3,[6][7][8][9]46,[49][50][51] These new endothelial cells circulate and ultimately contribute to blood vessel formation during tumor development and metastasis. 49,52 However, the origin of cells that ultimately line tumor blood vessels and specific proteins required for tumor vasculogenesis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…59 In this study, we have defined the critical role of PTN in tumor-directed blood vessel formation uncovering a novel mechanism of tumor vasculogenesis involving transdifferentiation of monocytes into VECs that become incorporated into tumor blood vessels. In a recent study in collaboration with members of our group, 50 it was also shown that Ptn introduced into cells of a monocyte cell line induces their expression of VEC genes that incorporate into developing normal vasculature. We have now For personal use only.…”
Section: Org Frommentioning
confidence: 92%
“…PTN-induced transdifferentiation of macrophages has been shown to be regulated at the transcription level by GATA-2 and GATA-3. 109 Transdifferentiation of macrophage to other cell lineages, thus, cannot be ruled out, and reports in this direction will help us to understand macrophage plasticity more vividly.…”
Section: Transdifferentiationmentioning
confidence: 99%
“…The authors demonstrated that under in vivo conditions in mice, the monocytic cells that express PTN get integrated into blood vessels. 109 Tumor-infiltrating macrophages and TAMs have been described as suppressor macrophages that display anti-inflammatory and immunosuppressive activities. 110,111 In vivo delivery of IL-12 to tumor sites results in the conversion of tumor-infiltrating macrophages and TAMs from the anti-inflammatory phenotype to the proinflammatory phenotype.…”
Section: Reprogrammingmentioning
confidence: 99%
“…21 Transdifferentiation of monocytes and macrophages to functional endothelial cells has been demonstrated by overexpression of proteins like vascular endothelial growth factor (VEGF) 21 and pleiotrophin. 22 This in vivo reprogramming of cellular identity using direct transdifferentiation strategies has been also demonstrated in the mouse brain, Figure 1 A schematic timeline of the history of regeneration, stem cell research, cellular transition, and cell reprogramming. Although these areas of research were initially considered to be different, they now form an integral part of regenerative medicine.…”
Section: Macrophage Fate At the Site Of Tissue Repairmentioning
confidence: 81%